Kemampuan Computational Thinking Materi Fungsi Eksponensial Menggunakan Problem Based Learning - Hauda, Nabilah; Mulyono, Budi; Hapizah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
The development of technology in the 21st era is growing very rapidly, especially in the field of education. Learners are required to be able to hone skills, one of which is Computational Thinking (CT). This study aims to describe the emergence of indicators of students' CT ability through problem-based learning on exponential functions. This research is a descriptive qualitative research with the research subject, namely class X students of SMA Negeri 10 Palembang as many as 50 students with the focus of the subject, namely 3 students who have high, medium, and low abilities.. This research was conducted through preparation, implementation, and data analysis stages. The data in this study were collected through written tests and interviews with the aim of measuring students' CT abilities. The results obtained will be analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the indicators of students' CT abilities on exponential function material were well seen, namely decomposition, pattern recognition, and abstraction. As for algorithm indicators, students are still not precise in solving problems systematically with the right answers. The development of technology in the 21st era is growing very rapidly, especially in the field of education. Learners are required to be able to hone skills, one of which is Computational Thinking (CT). This study aims to describe the emergence of indicators of students' CT ability through problem-based learning on exponential functions. This research is a descriptive qualitative research with the research subject, namely class X students of SMA Negeri 10 Palembang as many as 50 students with the focus of the subject, namely 3 students who have high, medium, and low abilities.. This research was conducted through preparation, implementation, and data analysis stages. The data in this study were collected through written tests and interviews with the aim of measuring students' CT abilities. The results obtained will be analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the indicators of students' CT abilities on exponential function material were well seen, namely decomposition, pattern recognition, and abstraction. As for algorithm indicators, students are still not precise in solving problems systematically with the right answers. Keywords: Computational Thinking Ability, Exponential Function, Problem Based Learning.